2010
DOI: 10.1186/1756-9966-29-104
|View full text |Cite
|
Sign up to set email alerts
|

PKCα-induced drug resistance in pancreatic cancer cells is associated with transforming growth factor-β1

Abstract: BackgroundDrug resistance remains a great challenge in the treatment of pancreatic cancer. The goal of this study was to determine whether TGF-β1 is associated with drug resistance in pancreatic cancer.MethodsPancreatic cancer BxPC3 cells were stably transfected with TGF-β1 cDNA. Cellular morphology and cell cycle were determined and the suppressive subtracted hybridization (SSH) assay was performed to identify differentially expressed genes induced by TGF-β1. Western blotting and immunohistochemistry were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Although this is the first evidence for the involvement of these two PKC isozymes in resistance to this targeted molecular therapy, altered expression of PKCa and PKCd has been detected in several cancer cell types. For example, elevation of PKCa expression or activity has been reported in pancreatic, colon, prostate, glioma, and gastric cancer cells resistant to chemotherapeutic drugs, including cisplatin, doxorubicin, and vincristine (Matsumoto et al, 1995;Wu et al, 2009;Chen et al, 2010;Zhao et al, 2012). Interestingly, comparable to what we observed in erlotinib-resistant cells, continuous exposure of MCF-7 breast cancer cells to tamoxifen rendered high levels of PKCa and downregulation of PKCd (Li et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although this is the first evidence for the involvement of these two PKC isozymes in resistance to this targeted molecular therapy, altered expression of PKCa and PKCd has been detected in several cancer cell types. For example, elevation of PKCa expression or activity has been reported in pancreatic, colon, prostate, glioma, and gastric cancer cells resistant to chemotherapeutic drugs, including cisplatin, doxorubicin, and vincristine (Matsumoto et al, 1995;Wu et al, 2009;Chen et al, 2010;Zhao et al, 2012). Interestingly, comparable to what we observed in erlotinib-resistant cells, continuous exposure of MCF-7 breast cancer cells to tamoxifen rendered high levels of PKCa and downregulation of PKCd (Li et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…To assess a potential association between altered PKCa expression and erlotinib resistance, we used both pharmacological and RNAi approaches. Because PKCa has been implicated in drug resistance in some cancer types (Chen et al, 2010;Lee et al, 2012;Zhao et al, 2012) and its levels are strikingly high in erlotinib-resistant cells, we speculated that this PKC could be involved in acquired resistance to erlotinib in NSCLC cells. Initial experiments showed that treatment of H1650-M3 cells with the pan-PKC inhibitor GF109203X increases their sensitivity to erlotinib (10 mM) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PKC isozymes and cancer, PKC isozymes, especially PKC and , are involved in the Pgp-mediated MDR in several types of cancer, such as colon cancer [119][120][121], pancreatic cancer [399], gastric cancer [157], breast cancer [55], leukemia [513], and prostate cancer [447]. In general, inhibition of PKC isozymes that regulate P-gp leads to reduced MDR and enhanced cancer cell apoptosis.…”
Section: Pkc Isozymes and Mdrmentioning
confidence: 99%
“…These signaling responses stimulated by PKC activation lead to the downregulation of tight junction functions and enhanced antiapoptosis capabilities, which may increase cell invasion and metastasis [397,398]. TGF-1-mediated PKC activation reduces the sensitivity of pancreatic cancer cells to cisplatin through overexpression of P-gp [399], stimulates cell migration, and reduces the expression of a putative tumor suppressor, phosphatase, and tensin homology [400]. In addition, PKC has been shown to be involved in growth and differentiation of pancreatic cancer cells as the selective downregulation of PKC enhances TNFinduced growth arrest and differentiation in HPAC cells [401] and blocks retinoic acid-stimulated growth of the pancreatic cancer cell line AsPc1 [402].…”
Section: Ovarianmentioning
confidence: 99%
“…[27][28][29] Reports from different research groups have argued that multidrug resistance-associated protein 2 (MDRP2), 30 IAP family proteins, 31 RAF/ERK, 32 Akt/ mTOR, 33 heatshock protein 27 (HSP27), 34 PKC, 35 Wnt/ βcatenin, 36 and microRNAs 37 are involved in pancreatic cancer resistance. Therefore, it is important to define the intracellular molecular targets that may contribute to new therapies.…”
Section: Discussionmentioning
confidence: 99%